2018
DOI: 10.1038/s41372-018-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection is common in VLBW infants

Abstract: UTI is a significant cause of infection in VLBW infants. Urine culture should be included in all LOS evaluations in order to facilitate accurate diagnosis and appropriate antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…The incidence of infection and the organism distribution we report are consistent with other reports of VLBW late-onset sepsis in the time period studied, with 23% incidence of BSI and a predominance of CONS. [7][8][9] UTIs are common beyond day 3 of age, [10][11][12] and the number of VLBW infants in our study diagnosed with this infection was 10%, similar to previously reported rates 13,14 A lack of guidelines or incomplete adherence to guidelines among NICUs as to whether to obtain a urine culture when getting a blood culture for infants with suspected infection is one explanation for the practice variation we observed among centers. For the 30 cases of UTI, no blood culture results were reported, yet we found that 23% of UTIs were associated with bacteremia.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of infection and the organism distribution we report are consistent with other reports of VLBW late-onset sepsis in the time period studied, with 23% incidence of BSI and a predominance of CONS. [7][8][9] UTIs are common beyond day 3 of age, [10][11][12] and the number of VLBW infants in our study diagnosed with this infection was 10%, similar to previously reported rates 13,14 A lack of guidelines or incomplete adherence to guidelines among NICUs as to whether to obtain a urine culture when getting a blood culture for infants with suspected infection is one explanation for the practice variation we observed among centers. For the 30 cases of UTI, no blood culture results were reported, yet we found that 23% of UTIs were associated with bacteremia.…”
Section: Discussionsupporting
confidence: 87%
“…was also the most common pathogen in a single-center study of 762 VLBW infants with 66 UTIs identified between 1990 and 2001 13 and another singlecenter study of 232 VLBW infants with 32 UTIs identified between 2005 and 2015. 12 Other studies have shown E. coli to be the most common pathogen, including a single-center study of 572 VBLW infants with 20 UTIs identified conducted between 2004 and 2006. 2 The rate of Enterococcus spp.-positive urine cultures in this cohort was similar to previous studies completed in premature infants, which showed Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration of hospitalization has been shown to be associated with UTI diagnosis, which is confirmed here. 11,12 Infants with longer lengths of hospitalization have greater opportunity to develop and be diagnosed with a UTI, and likely have greater severity of illness, which may also be associated with increased UTI risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of UTIs in the entire study population was found to be 1.3%, which is lower than other published rates in similar populations. [7][8][9] Although the UTI frequency considerably increased from 0.75% preintervention to 4.18% post-intervention, both are potentially underestimated because of the failure to obtain urine cultures leading to missed UTIs, especially in the preintervention period. When looking only at infants in whom urine cultures were sent, the rate of UTI's was 35 and 42.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%